2014
DOI: 10.1007/s11512-013-0184-1
|View full text |Cite
|
Sign up to set email alerts
|

Monomial ideals whose depth function has any given number of strict local maxima

Abstract: We construct monomial ideals with the property that their depth function has any given number of strict local maxima.1991 Mathematics Subject Classification. 13A15, 13C13.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 15 publications
0
28
0
Order By: Relevance
“…While it is known by a classical result of Brodmann [2] that f (k) for k ≫ 0 is constant, the behavior of f (k) is not so well understood for initial values of k. In [8], it is shown that any non-decreasing bounded integer function f (k) is the depth function of a suitable monomial ideal and it is conjectured that f (k) can be any convergent nonnegative integer valued function. In support of this conjecture, it was shown in [1] that f (k) may have arbitrarily many local maxima. On the other hand, it seems that the depth function for the edge ideals behave more tamely.…”
Section: Introductionmentioning
confidence: 82%
“…While it is known by a classical result of Brodmann [2] that f (k) for k ≫ 0 is constant, the behavior of f (k) is not so well understood for initial values of k. In [8], it is shown that any non-decreasing bounded integer function f (k) is the depth function of a suitable monomial ideal and it is conjectured that f (k) can be any convergent nonnegative integer valued function. In support of this conjecture, it was shown in [1] that f (k) may have arbitrarily many local maxima. On the other hand, it seems that the depth function for the edge ideals behave more tamely.…”
Section: Introductionmentioning
confidence: 82%
“…In general, we may have Ass I t ⊆ Ass I t+1 (see e.g. [1,13,15]). It has been of great interest to know when Ass I t ⊆ Ass I t+1 for all t ≥ 1 (see e.g.…”
Section: Depth and Regularity Functionsmentioning
confidence: 99%
“…Let R=k[x 1 , ..., x n ] be a polynomial ring over a given field k, and let I be a homogeneous ideal in R. It is known by Brodmann [3] that depth(R/I s ) takes a constant value for large s. Moreover, Two natural questions arise from Brodmann's theorem: (1) What is the nature of the function s →depth R/I s for s dstab(I)? (2) What is a reasonable bound for dstab(I)?…”
Section: Introductionmentioning
confidence: 99%
“…[1]). Squarefree monomial ideals behave considerably better than monomial ideals in general, and Herzog and Hibi [10] asked whether depth functions of any squarefree monomial I is non-increasing, that is depth R/I s depth R/I s+1 for all s 1.…”
Section: Introductionmentioning
confidence: 99%